2008
DOI: 10.1007/s00467-008-0929-4
|View full text |Cite
|
Sign up to set email alerts
|

Low bone density in children with hypercalciuria and/or nephrolithiasis

Abstract: The objective of this study was to identify how many children with hypercalciuria and/or nephrolithiasis have a low bone density and whether the risk of low bone density can be identified by 24-h urine stone-risk profiles and/or growth parameters. A retrospective chart review was performed on 110 idiopathic hypercalciuria and/or kidney stone patients who received both a 24-h urine for stone-risk profile and a dual-energy X-ray densitometry scan. Patients were divided into low bone density vs. normal bone densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 38 publications
(41 reference statements)
5
31
0
4
Order By: Relevance
“…In a previous study, our group determined that 30% of the 73 hypercalciuric children investigated showed signs of osteopenia [2]. This association of osteopenia and IH was later confirmed by Freundlich et al [3], Penido et al [4], and Schwaderer et al [5], who respectively reported that 38, 37, and 47% of the IH children studied showed a significant decrease in BMD.…”
Section: Introductionsupporting
confidence: 71%
“…In a previous study, our group determined that 30% of the 73 hypercalciuric children investigated showed signs of osteopenia [2]. This association of osteopenia and IH was later confirmed by Freundlich et al [3], Penido et al [4], and Schwaderer et al [5], who respectively reported that 38, 37, and 47% of the IH children studied showed a significant decrease in BMD.…”
Section: Introductionsupporting
confidence: 71%
“…Increased rates of low BMD and increased carotid artery wall thickness have also been identified in preliminary studies of children and adults with USD (9)(10)(11)(12). USD is also associated with CKD, diabetes mellitus, and hypertension (13,14).…”
Section: Epidemiologymentioning
confidence: 85%
“…The main reason is the fact of being considered as a supplement, but studies with more detailed information on its effects in the pediatric population are lacking [102] . Studies by Reusz et al [103] and Schwaderer et al [104] demonstrated the beneficial effects of thiazides and/or potassium citrate on bone mineral density in children with IH. According to Srivastava et al [102] , drug therapy should be reserved for children with symptomatic hypercalcuria and/or rare monogenic disorders.…”
Section: Idiopathic Calcium Stonesmentioning
confidence: 99%